Pendekatan Sosio-Kultural dalam Pengelolaan Isu Eksternal (Studi Kasus pada Sebuah Pesantren) - Nia Miftakhul Jannah; Maulina Pia Wulandari; Bambang Dwi Prasetyo (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze how Islamic boarding schools implement communication strategies in dealing with the issue of sexual violence by focusing on two main dimensions, namely personification and adaptation. This study uses a qualitative case study method, this study collects data through in-depth interviews with Islamic boarding school policy makers, as well as documentation analysis related to the communication strategies implemented. The results of the study indicate that the personification dimension plays an important role in building public trust, where Islamic boarding school leaders act as representatives of the institution in conveying consistent and credible narratives. Meanwhile, the adaptation dimension allows flexibility in communication strategies, including the use of digital media, the involvement of religious figures, and discussion-based approaches to reduce the potential for conflict escalation. The conclusion of this study confirms that the combination of strong leadership and appropriate adaptability is key to maintaining the legitimacy and reputation of Islamic boarding schools in the midst of an external crisis. These findings contribute to the development of a crisis communication model for religious-based institutions, especially in facing social challenges in the digital era. Keywords: Issue Management, Pesantren, Public Relations, Socio-Cultural